Studies on Drought Tolerant and High Yielding Groundnut Varieties in Perambalur District - Punithavathi, M.; Vasanthakumar, R.; Mariappan, V. Nethaji (International Journal of Bio-resource and Stress Management, 2021)
Three varieties of groundnut were used to assess the drought tolerance and high yielding potential. Groundnut (Arachis hypogaea L.) is an important oil seed crop mainly grown under rainfed situation. Erratic rainfall and frequent drought during the crop growth period, groundnut yields are generally low under rainfed conditions. Drought during critical crop growth stages is crucial for loss in yield of groundnut varieties. But tolerant genotypes may give better yield due to maintenance of physiological responses that were triggered during drought. On Farm Trials was conducted by Krishi Vigyan Kendra, Hansroever campus, Perambalur district in Tamilnadu, India to assess suitable drought tolerant and high yielding groundnut variety in terms of yield, acceptability and adoption potential during rabi 2018-19 in Perambalur district, India. Three varieties of groundnut were used to assess the drought tolerance and high yielding potential viz., Dharani, Co7 and TMV 7. The study revealed that Dharani recorded higher pod yield (2402 kg ha-1), higher number of pods plant-1 (26) and optimum plant population (26.3 plants m-2) as compared to farmers practice. The groundnut variety Dharani resulted in the highest shelling percentage (75%), while the lowest was registered with TMV 7. Gross and net returns were Rs. 115324 and Rs. 66593 ha-1, respectively by cultivating Dharani as against Rs. 87523 and Rs. 41550 ha-1 in the check variety. Dharani and Co7 would be a better option forrainfed cultivation in Perambalur district.